Asymptomatic bacteriuria in antenatal cases and its effects on obstetrical outcome - Narang, Ridhi; K. Nandmer, Gurpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Urinary tract infection is the second most common bacterial infection seen during pregnancy and is due to the morphological and physiological changes that take place in the genitourinary tract. The pregnant women are two times more commonly affected than age matched non pregnant females and it may lead to less favorable pregnancy outcomes and complications such as premature birth, low birth weight, pyelonephritis, preeclampsia and anemia. Methods: This hospital based cross sectional study was conducted on 350 pregnant women, falling into the inclusion criteria of the study, who attended the antenatal clinic in the Department of Obstetrics and Gynecology at PCMS and RC, Bhopal, irrespective of the gestational age of the cases. The cases found to have asymptomatic bacteriuria were followed till delivery and any adverse antenatal or perinatal outcome was noted. Results: The study was conducted with the aim to know the prevalence of asymptomatic bacteriuria and the obstetrical outcome in pregnant women. The prevalence of asymptomatic bacteriuria was 13% and it was common in the age group of 21-25 years, in primigravidas and with period of gestation less than 12 weeks. E. coli was found to be the commonest causative organism. Asymptomatic bacteriuria was found significantly associated with the presence of anemia. Maternal morbidity in terms of pre term labour was higher in cases with asymptomatic bacteriuria. Conclusions: Urine culture and sensitivity should be done as a routine investigation to screen the patients for asymptomatic bacteriuria and to prevent adverse maternal and fetal outcomes.